Pemetaan lanskap global penelitian ketahanan mental: Tren, kontribusi, dan tema kunci (2014-2024) - Noor Akhmad; Maulidin Maulidin; Fadli Zainuddin (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze trends, contributions, and key themes in mental toughness research using a bibliometric approach. Data were retrieved from Scopus with the search query TITLE-ABS-KEY (